Kendala-Kendala Pendeteksian Praktik Insider Trading dalam Transaksi Saham di Bursa Efek - Ridwan Khairandy (Jurnal Hukum IUS QUIA IUSTUM, 2004)
Before the investor made his decision rationally for purchasing or buying the stock exchange in general, he examines first the condition of company involved. That is why, the transparency principle is the most important matter in transaction in stock exchange. Although, carrying out the transparency principles are sometimes create the handicaps through Insider trading practices and it is sometimes difficult to besolve with law perspective. The difficulties are caused bythe weak oflaw instrument and the borderless about when public arebe able to show the fact materially and openly.